2019
DOI: 10.1039/c9cy00705a
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of furfuryl alcohol from furfural: catalytic performance of monometallic and bimetallic Mo and Ru phosphides

Abstract: The catalytic properties of monometallic and bimetallic Ru and Mo phosphides were evaluated for their ability to selectively hydrogenate furfural to furfuryl alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 96 publications
2
30
2
Order By: Relevance
“…Moreover, TPR of C 6 H 6 also suggests that P atoms significantly decrease the C 6 H 6 binding energy and extent of C 6 H 6 decomposition in comparison to Ru(0001), which can promote C 6 H 6 desorption over decomposition and lead to decreased coking during TPR of C 6 H 10 (Figure S3). While these results indicate that the presence of P atoms within the P 0.4 -Ru­(0001) surface withdraw charge from Ru atoms, consistent with XPS of related TMP nanoparticles, Muetterties et al demonstrated that adsorption of trimethyl phosphine could liberate reactive intermediates of dehydrogenation reactions from Ni , and Pt surfaces. To further understand the dehydrogenation selectivity and intrinsic barriers, we probe the mechanism of C 6 H 10 dehydrogenation over Ru(0001) and P 0.4 -Ru­(0001).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Moreover, TPR of C 6 H 6 also suggests that P atoms significantly decrease the C 6 H 6 binding energy and extent of C 6 H 6 decomposition in comparison to Ru(0001), which can promote C 6 H 6 desorption over decomposition and lead to decreased coking during TPR of C 6 H 10 (Figure S3). While these results indicate that the presence of P atoms within the P 0.4 -Ru­(0001) surface withdraw charge from Ru atoms, consistent with XPS of related TMP nanoparticles, Muetterties et al demonstrated that adsorption of trimethyl phosphine could liberate reactive intermediates of dehydrogenation reactions from Ni , and Pt surfaces. To further understand the dehydrogenation selectivity and intrinsic barriers, we probe the mechanism of C 6 H 10 dehydrogenation over Ru(0001) and P 0.4 -Ru­(0001).…”
Section: Resultsmentioning
confidence: 68%
“…Previously reported Bader charge analysis and differences among core-electron binding energies detected by X-ray photoelectron spectroscopy (XPS) and X-ray absorption near-edge structure demonstrate that charge transfers from transition metals to P in TMP, which results in electronic modifications of the transitions metals. These electronic modifications decrease the binding energy of the dehydrogenation product and facilitate the desorption of olefins over further dehydrogenation. In addition, these electronic changes can modify the binding modes and configuration of surface intermediates caused by interactions with cationic metal and anionic P atoms exposed at surfaces. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Current research in this area is focusing on the one-pot preparation of FAL from biomass, crude FUR as feedstock, and developing eco-friendly catalysts for this transformation [43]. There are dedicated reviews available on FAL; therefore, the readers are referred to those for comprehensive information [44,45].…”
Section: Catalytic Reduction Of Furfurals To Furanic Compoundsmentioning
confidence: 99%
“…The authors claimed that not only FUR can be hydrogenated to FuOH in this system, but various unsaturated aldehydes can be transformed to the corresponding unsaturated alcohols due to the synergy created between Ir metal and ReO x , which increases the selectivity and activity without losing the activity of the noble metals. Bonita et al [128] compared the conversion of FUR and the selectivity to FuOH in isopropanol, toluene and hexanes. It was noted that the FUR conversion and the selectivity to FuOH declined significantly in toluene and hexanes, compared to the system involving isopropanol.…”
Section: Effect Of Solvents In the Formation Of Furfuryl Alcoholmentioning
confidence: 99%